POTENSI USAHA TX TRAVEL SEMARANG - Syafira Al Dawiyah Mukti (Jurnal Pengabdian Masyarakat Waradin, 2022)
At this time the unemployment rate is increasing, even among scholars, unemployment reaches thousands of people. One of the reasons is that their bachelor's degree is not followed by reliable skills to enter an increasingly competitive world of work. Currently, along with the development of technology and science, we are required to be able to compete in the world of work by improving the quality of human resources who have good quality knowledge and good personality competencies and have skills that can be used in roles in society and the state in the field of education. the job he does.